The impact of the determinants of the financial structure on the capital structure of private commercial banks in Syria (Case study of Bemo Saudi Fransi Bank) (Journal of Hama University, 2021)
The study aimed to identify the most important determinants of the financial structure in the capital structure of Bemo Saudi Fransi Bank, during the period from 2009 to 2018, To reach more appropriate model of the most influential determinants in the formation of the capital structure of Bemo Saudi Fransi. The study analyses the impact of the determinants of the financial structure (profitability, liquidity, bank size, growth rate, tangible assets, risk, and tax on the capital structure by using quarterly financial reports, budgets and income statements of Bemo Saudi Fransi, using the simple regression analysis method to study The effect of each determinant separately on the capital structure, and then using the multiple regression method using the Stepwise method based on the statistical analysis program (SPSS 25). The results of the simple regression showed the existence of a statistically significant effect for each of (profitability, size, growth, tangible assets, risk) on the capital structure, while liquidity and tax did not have any significant effect on the capital structure when studying the effect of each variable. Separately.Whereas the results of multiple regression showed that some of the studied determinants, namely the growth and liquidity variables, did not have a statistically significant effect, and thus they were excluded from the model. Whereas, the study found that the other studied determinants (profitability, size, tangible assets, risk, tax) have a statistically significant impact on the capital.